Chlorophyll Breakdown in a Fern—Discovery of Phyllobilin Isomers with a Rearranged Carbon Skeleton. Issue 45 (11th October 2018) - Erhart, Theresia; Vergeiner, Stefan; Kreutz, Christoph; Kräutler, Bernhard; Müller, Thomas
Abstract: All structure‐based information on chlorophyll (Chl) breakdown in the higher plants relies on studies with angiosperms. Herein, the first investigation of a fern is reported, revealing a novel type of Chl catabolites (phyllobilins) in leaves of this large division of the vascular plants, and providing structural insights into an astounding metabolic process of the higher plants that appears to have played a role even in early phases of plant evolution. The tetrapyrrolic Chl catabolites in the cosmopolitan bracken fern were discovered to be phyllobilin isomers with an unprecedented skeleton, proposed to be the striking result of a rearrangement of a hypothetical phyllobilin precursor. Abstract : Skeleton key : The analysis of chlorophyll breakdown in leaves of a fern yields two iso ‐phyllobilanones. The formation of these novel catabolites requires a carbon‐skeleton rearrangement of a hypothetical precursor. This study provides new structural insights in chlorophyll breakdown in vascular plants and shows that this process played a role in early phases of plant evolution.